ECONOMETRIC ASSESSMENT OF THE IMPACT OF ECONOMIC INDICATORS ON THE NON-OBSERVED ECONOMY OF MOLDOVA - Stratan, Alexandru; Gutium, Tatiana (Economy and Sociology, 2022)
The non-observed economy is an integral part of the modern economic system. It is a threat to economic security in conditions of slow stagnation. The relevance of this study lies in the fact that the identification of factors influencing the non-observed economy makes it possible to develop proposals to combat this phenomenon. Also, this paper describes the problems that researchers in the Republic of Moldova face when econometrically modeling the dependence of the non-observed economy on socio-economic indicators. The novelty and purpose of the study is the construction of models with one equation, where the endogenous variable is the level of the non-observed economy in value terms and the share of the non-observed economy in Gross Domestic Product. The main research methods are regression analysis and economic and mathematical modeling. At the first step of the study, the identified main factors of influence that determine the size of the shadow economy in twenty-eight countries were systematized. In the next step, the authors established the available series of statistical data published by the National Bureau of Statistics and determined exogenous variables. The authors used the program for econometric analysis EViews 9 in constructing the models. The single equation models were tested inclusively for first and second-order autocorrelation and heteroscedasticity. The constructed models showed that the non-observed economy is positively affected by the growth of the main sectors of the national economy and by an increase in the unemployment rate. While the rise in foreign trade turnover, namely imports, negatively affects the endogenous variable. There is an identical (negative) relationship between the freight turnover and the level of the non-observed economy.